6 EVALUATION OF ECHOCARDIOGRAPHIC PARAMETERS IN PATIENTS WITH MICROVASCULAR DYSFUNCTION: A PROSPECTIVE STUDY. (15th December 2022) - Biancofiore, Antonio; Fineschi, Massimo; Cameli, Matteo; Gori, Tommaso
Abstract: Background: The prevalence of microvascular angina is underestimated in the general population because it is often difficult to detect. Microvascular dysfunction is defined by parameters of reduced coronary flow reserve (CFR <2) without epicardial stenosis and/or increased index of microvascular resistance (IMR> 25). Purpose: The aim of this study was to evaluate the echocardiographic parameters in patients with symptoms of myocardial ischemia without evident coronary epicardial obstruction. Primary endpoint was to analyze the global longitudinal strain of the left ventricle and the left atria strain in patients with microvascular angina. Secondary endpoint was to analyze echocardiographic parameters to evaluate the diastolic function of the left ventricle, the prevalence of cardiovascular risk factors and the blood tests values. Methods: Between 1st February 2019 and 1st May 2022, subjects with angina and not functionally significant epicardial stenosis (Resting Full-cycle Ratio > 0.91, Fractional flow reserve >0.80), underwent assessment of microvascular function and were divided into 2 cohorts. All patients had sinus rhythm, preserved left ventricular ejection fraction (LVEF> 55%), no severe left ventricular hypertrophy (interventricular septum <13 mm) or structural heart disease. For each patient we analyzed the left ventricular global longitudinal strain in the three apical views (4 chamber, 2 chamber and 3 chamber) and the left atria strain, PALS (peak atrial longitudinal strain) and PACS (peak atrial contraction strain), in two apical views (4 chamber and 2 chamber). We also measured the diastolic function indices (E/e', isovolumic relaxation time, deceleration time), the left atrial area and pulmonary artery systolic pressure (PASP) evaluated on echocardiography. Results: A total of 132 patients were enrolled. Of those, 47 had evidence of microvascular dysfunction and 85 had normal CFR/IMR. Primary Endpoint: patients with microvascular dysfunction had reduced values of left ventricular global longitudinal strain and reduced values of left atrial strain compared to controls (p<0, 001). Secondary Endpoint: a higher prevalence of diabetic and obese women was associated with microvascular dysfunction. However, there were no significant differences in age, prevalence of hypertension, dyslipidemia, smoking and dysthyroidism. Numerically higher values of NTproB-type Natriuretic Peptide (NTproBNP) and C-reactive protein were seen in patients with microvascular dysfunction, while there were no significant differences in hemoglobin, white bold cells, platelets, cholesterol, creatinine and troponin values. Left ventricular isovolumic relaxation time, left atrium area, and pulmonary artery systolic pressure as well as E/e' values were significantly increased in patients with microvascular dysfunction. Furthermore, there was a significant reduction in deceleration time values. Conclusion: Patient with microvascular dysfunction are frequently diabetic and obese women. Echocardiographic parameters show left ventricular diastolic dysfunction and possibly subsequent left atrial remodeling. Furthermore, the analysis of the global longitudinal strain of the left ventricle could reveal alterations in cardiac contractile mechanics that are difficult to identify with conventional echocardiography. NTproBNP values were not significantly higher, demonstrating that patients with microvascular dysfunction have an early diastolic dysfunction that is not clinically evident.